Gender and the Black Jobs Crisis. Issue 1 (14th March 2016) - Burnham, Linda
Abstract : Black women face a jobs crisis characterized by over-concentration in low-wage occupations, high rates of unemployment, both racial and gender gaps in wages, and lingering impacts of the recession. Lesbian, gay, bisexual, transgender, and queer (LGBTQ) workers who are Black face particular challenges in the workforce and report income levels much lower and poverty rates much higher than White LGBTQ workers. The gendered dimensions of the Black jobs crisis require advocacy and policy interventions that reward Black women for their contributions to the U.S. economy.